Intergenerational class mobility among men and women in Europe: Gender differences or gender similarities? - Bukodi, E; Paskov, M (Oxford University Press, 2020)
In this article, we address two inter-related questions. Are there gender differences in the level and the pattern of intergenerational class mobility? If so, do these differences show up in a uniform fashion in Europe? To answer these questions, we use a newly constructed comparative data set that allows us to examine how far differences between men and women in absolute and relative mobility can still be characterized in the same way as in the last decades of the 20th century. We also examine the effects of women’s heterogeneity in terms of labour market attachment on their class mobility. Our results show that in most countries, women are more likely than men to be found in different class positions to those of their parents’. But we point out that the reasons for this might be quite different in the West and in the East. As regards relative mobility chances, we are able to underwrite the dominant finding of past research that women display greater social fluidity than men only in a certain group of countries. In most countries, we do not find any systematic and uniform gender difference between men and women in the level of their relative mobility rates. But, we do find significant and systematic gender differences in the pattern of relative rates: women’s class mobility appears to be more impeded by hierarchical barriers than by the propensity for class inheritance. And, in this regard, our findings point to a large degree of commonality across European countries.